Zero-field J-spectroscopy of quadrupolar nuclei - Picazo-Frutos, Román; Sheberstov, Kirill F.; Blanchard, John; Van Dyke, Erik; Reh, Moritz; Sjoelander, Tobias; Pines, Alexander; Budker, Dmitry; Barskiy, Danila A. (Nature Communications, 2024)
Zero- to ultralow-field nuclear magnetic resonance (ZULF NMR) allows molecular structure elucidation via measurement of electron-mediated spin-spin J-couplings. This study examines zero-field J-spectra from molecules with quadrupolar nuclei, exemplified by solutions of various isotopologues of ammonium cations. The spectra reveal differences between various isotopologues upon extracting precise J-coupling values from pulse-acquire measurements.